The Effect of Religious Instrumental Music Therapy on Anxiety in Breast Cancer Patients - Chyntia Ramadhana Fahira; Idrawati Bahar; Tasman (Journal of Applied Holistic Nursing Science, 2025)
Background: Anxiety is a vague and uneasy feeling caused by discomfort or fear accompanied by a response. Anxiety in breast cancer patients is a psychological disorder due to facing uncertainty, worries about the effects of cancer treatment, and fear of disease progression which may lead to death. This study aimed to determine the effect of instrumental music therapy on anxiety levels in breast cancer (ca mamae) patients undergoing chemotherapy at Dr. M. Djamil Hospital, Padang Methods: This research used a pre-experimental design with a one-group pre-test post-test design. Anxiety levels were measured using the HARS questionnaire. Samples were selected using a purposive sampling technique, and data were analyzed using the T-test. Results: The results showed that the average anxiety score before the intervention was 26.79, and after the intervention, it was 19.07. There was a significant difference in anxiety scores before and after the intervention with a p-value = 0.000 (p < 0.05), indicating a significant effect of the intervention. Conclusion: In conclusion, instrumental music therapy had an effect on reducing anxiety in breast cancer patients undergoing chemotherapy. It is recommended that nurses in chemotherapy wards consider instrumental music therapy as a non-pharmacological intervention to help reduce anxiety levels in patients undergoing chemotherapy